An enhanced MAC protocol based on the IEEE 802.11 for data relay satellite systems. (3rd January 2020) - Wang, Xingyu; Zhao, Shanghong; Li, Yongjun; Zhu, Zhuodan; Zheng, Yongxing; Yu, Chen
Summary: Data relay satellite (DRS) systems play an important role in space information networks. Characterized by highly dynamic topology and discontinuous communication links, it is suggested that the IEEE 802.11 protocol employed in such a network could be more flexible. However, such a terrestrial network protocol could not be applied to DRS systems directly, nor supports a fast response due to the long propagation delay and severe packet collision. To address this challenge, we proposed an enhanced media access control (MAC) protocol based on the IEEE 802.11 protocol providing multiaccess for low earth orbit (LEO) distributed constellations. In this paper, we investigated the access delay performance of the proposed protocol in our model. Then, we derived a contention window adaption by using an iteration algorithm that can dynamically adjust the values of the contention window depending on the number of user satellites in the communication coverage. Simulation results show that the average access delay does not exceed 20 seconds, which is significantly lower than the standard protocol. Moreover, the traffic threshold is increased to 0.6, and the maximum throughput has doubled compared with the standard protocol. It is proved that the enhanced MAC protocol shows a better performance in DRS systems. Abstract : Characterized by highly dynamic topology and discontinuous communication links, it is suggested that the IEEE 802.11 protocol employed in space information networks could be more flexible. However, such a terrestrial network protocol could not apply to DRS systems directly, nor supports a fast response due to the long propagation delay and severe packet collision. To address this challenge, we proposed an enhanced MAC protocol based on the IEEE 802.11 protocol providing multiaccess for low earth orbit (LEO) distributed constellations.